Continuous monitoring of EDTA extractable iron from mineral slurries using a microfluidic chip. (6th March 2022) - Yang, Daisy; Shallan, Aliaa I.; Breadmore, Michael C.; Greet, Christopher; Priest, Craig
Abstract: In mineral processing, iron oxidation species formed on the mineral surface play a dominant role in depressing mineral flotation and must be monitored. Current analytical methods rely on off‐line sample preparation followed by conventional analytical techniques, which are labour intensive and time delayed. This paper reports the successful application of an open microfluidic chip for real‐time continuous monitoring of ethylenediaminetetraacetic acid (EDTA) extractable iron (derived from iron oxidation species) in mineral slurries. A detailed mineralogical study of the mineral ore before and after leaching by EDTA has been undertaken to understand the leaching behaviour of the EDTA‐slurry extraction system, showing good agreement with solution analysis.